Estudo de quantificação dos compostos fenólicos, avaliação das atividades antioxidante e antimicrobiana da casca do caule do Croton cajucara Benth - SOUZA, Alexandre Augusto Moraes de (2019)
The main objective of this work was to analyze the yield (on a dry basis), to quantify the phenolic compounds, and to evaluate antioxidant and antimicrobial the activity of Croton cajucara BENTH stem bark extracts. For this, a conventional extraction was carried out using a stainless steel extractor which followed the experimental planning (Box Hunter and Hunter ) of two factors and two levels, being the temperature (50 °C and 60 °C) and granulometry (0,10 mm and 0,51 mm) of the botanical material, to determine which variables influenced in the extraction process. To the quantification of phenolic compounds was used the methodology of Folin-Ciocalteau for the analysis of the antioxidant activity the IC50 method was applied and for the antimicrobial analysis the microdilution method was employed to indicate the Minimum Inhibitory Concentration (MIC) against the bacterial strains, Staphylococcus aureus, Proteus mirabilis, Pseudomonas aeruginosa and Salmonella typhi, as well as fungal strain, Candida albicans. The maximum and minimum yields were respectively to the runs 6 (T = 60 °C, G = 0,10 mm) with 9.11% and 5 (T = 50 °C, G = 0,10 mm) with 5.15%. In the quantification of phenolic compounds, run 4 (T = 60 °C, G = 0,51 mm) showed a maximum value and the minimum was the 6 (T = 60 °C, G = 0,10 mm), with 50.32 and 26.98 mgEAG/g, respectively. In relation to the antioxidant activity, the results were expressed as IC50 and ranged from 9,01 % (Test 6, T = 60 °C, G = 0,10 mm) to 14.03% (test 7, T = 50 ° C; G = 0,51 mm). For the antimicrobial activity, the extracts did not inhibited the growth of the bacterias and fungus tested, presenting a MIC > 1.000 μg/mL. All the results were treated statistically and, in general, proved that the best extraction conditions were T = 60 ° C and G = 0,10 mm.